School libraries role in connected learning: perception of school librarians in Nigeria (2021)
Connected learning (CL) aims at bridging the gap between in-school and out-of-school learning, thus, learning now takes place not only in the classroom setting. Libraries as nexus of informal learning space are appropriate spaces for connected learning. Observation shows that CL has not been embraced in Nigeria. Therefore, this study examined the perception of school librarians on the roles of school libraries in CL, challenges of CL, and solutions. School librarians that attended the national workshop organized by the Nigerian School Library Association (NSLA) participated in the focus group discussion. The findings revealed perceived roles of school libraries in CL, challenges of CL in Nigeria, and solutions proffered.